The Effect of Aerobic Exercise Models and Sports Motivation on Decreasing the Body Fat Procentage - Setiawan, Iwan (Department of Physical Education, Sport, Health and Recreation, 2019)
The purpose of this study was to determine the effect of low impact aerobic exercise training models, and bench models also exercise motivation on decreasing percentage of body fat. This research was conducted at one of the fitness centers in Jakarta. This research is planned to take place for three months with activities covering the testing of research instruments, initial data collection for sample grouping, experimentation and final data collection. This study uses an experimental method with a simple 2 X 2 factorial design. After the data collection is done, based on the data obtained, the results of hypothesis testing and discussion of research results can be summarized as follows: 1) there are significant differences between low impact aerobics models and bench models against decrease in percentage of body fat, bench training model is better than low impact training on decreasing percentage of body fat; 2) there is a difference in the decrease in body fat percentage between bench exercise models and low impact exercises for high-motivated sports groups. In other words, members who have high sports motivation tend to use the exercise bench model; 3) Members who have low sports motivation tend to use the low impact exercise model better than the bench exercise model in decreasing the percentage of body fat; 4) There is an interaction between the exercise model and exercise motivation to decrease the percentage of body fat.